Motivos que levaram empresas de Santa Rita do Sapucaí/MG a não migrarem para o Paraguai, mesmo com condições de incentivos fiscais - Martins, Lucas Pessi (2021)
The migration of companies to Paraguay has been treated as a concern for some time by the Brazilian government. Many of the companies that migrate to the neighboring country, aim to reduce the economic costs of their activities, however, in 2016, businessmen from the city of Santa Rita do Sapucaí / MG visited Paraguay in order to learn more about the conditions and economic benefits granted by the Paraguay government, and shortly after the visit, none of these companies moved. Thus, the problem of this research was raised and, in due course, the hypotheses that guide this study. It is believed that some Brazilian companies do not migrate to Paraguay due to the fact that the conditions of economic benefits are not sufficient to cover the transaction costs arising and institutional factors, country risk, asset and tax specificities. Transaction costs are different from economic costs and for this reason it is not considered most of the time in decision-making processes. Therefore, interviews with some businessmen who were present in Paraguay in 2016 will be used to collect the data for this research. Soon afterwards, the techniques of content analysis were used to process the data. It can be seen in this study that the companies in question chose not to migrate to Paraguay due to the fact that transactional costs such as energy distribution conditions, transportation, unskilled labor are worrying and exceed the benefits granted by the Regime of Maquila. In addition, all the companies in this study had, at the time of the study, an ICMS tax benefit granted by the Minas Gerais government, a fact that also had an impact on the decision to stay in Brazil.